Acoustic manipulation of microparticle in a cylindrical tube for 3D printing - Sriphutkiat, Yannapol (2020)
Purpose: The capability of microparticle/objects patterning in the three-dimensional (3D) printing structure could improve its performance and functionalities. This paper aims to propose and evaluate a novel acoustic manipulation approach. Design/methodology/approach: A novel method to accumulate the microparticles in the cylindrical tube during the 3D printing process is proposed by acoustically exciting the structural vibration of the cylindrical tube at a specific frequency, and subsequently, focusing the 50-μm polystyrene microparticles at the produced pressure node toward the center of the tube by the acoustic radiation force. To realize this solution, a piezoceramic plate was glued to the outside wall of a cylindrical glass tube with a tapered nozzle. The accumulation of microparticles in the tube and printing structure was monitored microscopically and the accumulation time and width were quantitatively evaluated. Furthermore, the application of such technology was also evaluated in the L929 and PC-12 cells suspended in the sodium alginate and gelatin methacryloyl. Findings: The measured location of pressure and the excitation frequency of the cylindrical glass tube (172 kHz) agreed quite well with our numerical simulation (168 kHz). Acoustic excitation could effectively and consistently accumulate the microparticles. It is found that the accumulation time and width of microparticles in the tube increase with the concentration of sodium alginate and microparticles in the ink. As a result, the microparticles are concentrated mostly in the central part of the printing structure. In comparison to the conventional printing strategy, acoustic excitation could significantly reduce the width of accumulated microparticles in the printing structure (p < 0.05). In addition, the possibility of high harmonics (385 and 657 kHz) was also explored. L929 and PC-12 cells suspended in the hydrogel can also be accumulated successfully. Originality/value: This paper proves that the proposed acoustic approach is able to increase the accuracy of printing capability at a low cost, easy configuration and low power output.